2010
DOI: 10.5120/319-487
|View full text |Cite
|
Sign up to set email alerts
|

Ant Colony Optimization Technique Applied in Network Routing Problem

Abstract: ABSTRACT:In this paper, the Ant Colony Optimization Technique has been applied in different network models with different number of nodes and structure to find the shortest path with optimum throughput. Three variations of the Ant Colony Optimization Technique, ACO1, ACO2 and ACO3 has been proposed and applied on different standard network models and the results has been analyzed and concluded. A Tabu list is also maintained for a network with large number of nodes and results were collected to find the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These networks are often deployed in remote or inaccessible areas, making it impractical to replace or recharge their batteries. The longevity of the network is directly influenced by its energy efficiency [28]. Consequently, the design of dependable and efficient sensor nodes and routing protocols becomes crucial.…”
Section: Challenges In Designing Of Wireless Sensor Networkmentioning
confidence: 99%
“…These networks are often deployed in remote or inaccessible areas, making it impractical to replace or recharge their batteries. The longevity of the network is directly influenced by its energy efficiency [28]. Consequently, the design of dependable and efficient sensor nodes and routing protocols becomes crucial.…”
Section: Challenges In Designing Of Wireless Sensor Networkmentioning
confidence: 99%
“…The basic concept taking place is that when ever a mishap occurs, immediately the incident is being informed to the other vehicles such that other mobile devices can vary their route to avoid the congestion. Debasmita Mukherjee et al [2], has presented an idea to discover the shortest available path by applying various Ant Colony Optimization Mechanisms. Here, with the help of protocol of routing, the selection of path by calculation is done.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, they have finally concluded that the Ant Colony Optimization (ACO) Technique is an efficient approach for VANET. Debasmita Mukherjee et al [9] proposed a system to find the shortest path by using optimal solution by applying different network models and different number of nodes and structure. They have used three mechanisms for this, which includes ACO1, ACO2 and ACO3, which has been applied on the above different network models, and their results have been concluded.…”
Section: Motivationmentioning
confidence: 99%